Digital pixel test structures implemented in a 65 nm CMOS process - Aglieri Rinella, Gianluca; Andronic, Anton; Antonelli, Matias; Aresti, Mauro; Baccomi, Roberto; Becht, Pascal; Beole, Stefania; Braach, Justus; Buckland, Matthew Daniel; Buschmann, Eric; Camerini, Paolo; Carnesecchi, Francesca; et al. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2023)
The ALICE ITS3 (Inner Tracking System 3) upgrade project and the CERN EP R&D on monolithic pixel sensors are investigating the feasibility of the Tower Partners Semiconductor Co. 65nm process for use in the next generation of vertex detectors. The ITS3 aims to employ wafer-scale Monolithic Active Pixel Sensors thinned down to 20-40µm and bent to form truly cylindrical half barrels. Among the first critical steps towards the realisation of this detector is to validate the sensor technology through extensive characterisation both in the laboratory and with in-beam measurements. The Digital Pixel Test Structure (DPTS) is one of the prototypes produced in the first sensor submission in this technology and has undergone a systematic measurement campaign whose details are presented in this article. The results confirm the goals of detection efficiency and non-ionising and ionising radiation hardness up to the expected levels for ALICE ITS3 and also demonstrate operation at ＋20°C and a detection efficiency of 99% for a DPTS irradiated with a dose of 10151MeV neq cm-2. Furthermore, spatial, timing and energy resolutions were measured at various settings and irradiation levels.
Online verfügbar: 4. August 2023, Artikelversion: 18. September 2023
Gesehen am 28.06.2024